Analytical Method Development and Validation for the Determination of Riociguat in Their Formulations by Lc-Ms/Ms - Meyyanathan SN (Journal of Global Pharma Technology, 2018)
Objective: The purpose of this study was to develop a simple, sensitive, precise, and rapid LC-MS/MS method for quantitative determination of anti-hypertensive drug Riociguat in its formulation using electrospray ionization in positive mode. Method: In this method, a zorbax (50mm x 4.6mm x 5µm) column with mobile phase 0.1% Formic acid: Acetonitrile (15:85, v/v) was used in the flow rate of 0.5mL/min. Results: The linearity range of Riociguat ranged from 10 to 110 ng/mL with the correlation coefficient of 0.9994. The method was validated as per the ICH guidelines. The limit of detection and quantification was found to be 3.5ng/mL and 10ng/mL, respectively. The recoveries of Riociguat at different concentration levels were found to be in the range of 97.34 % to 99.76 %. Conclusion: The proposed method was found to be simple, fast, accurate, and precise and can be applied for routine quality control analysis of Riociguat in formulations. The method proved to be selective, specific, sufficiently sensitivity, highly reproducible and robust for the analysis of formulation in Riociguat.Keywords: Formulation, Riociguat, LC-MS/MS, Validation.